PENGEMBANGAN SISTEM PEMBAYARAN PADA UNIVERSITAS ATMA JAYA MAKASSAR - Sumarta, Sean Coonery; Tungadi, Astrid Lestari; Tommy, Phe (TEMATIKA, Journal of Informatics and Information Systems, 2019)
The purpose of the research is to develop a payment system UAJM that can handle the process of installment payments and other tuition payments such as remedial payments, seminar results and examination results table. The research was carried out using the method of the design of the waterfall, it consists of a number of stages are carried out systematically.